(untitled) (Bangladesh Journal of Botany, 2020)
Two metal resistant Bacillus cereus strains (AVP12 and NC7401) isolated from metal polluted and nonpolluted rhizospheres of Tagetes minuta were examined for Cr(VI) bioaccumulation potential. It was found that the strains have potential to survive even at metal concentration of 300 mg/l. The per cent removal capacity of Cr(VI) by AVP12 and NC7401 strains was analyzed as a function of environmental factors including pH, incubation time and biosorbate concentration. The optimum pH was found to be 5 andwas selected for further studies. Both Langmuir and Freundlich isotherm models were found suitable for description of Cr(VI) bioaccumulation. The maximum Cr(VI) bioaccumulation capacity by Bacillus cereus AVP12 and Bacillus cereus NC7401 strains isolated from polluted rhizosphere was 181.0 and 107.5 mg/l, respectively while maximum Cr(VI) bioaccumulation capacity by Bacillus cereus AVP12 and Bacillus cereus NC7401 strains isolated from non-polluted rhizosphere was 92.59 and 62.11 mg/l, respectively. Both types of rhizobacterial strains, especially isolated from metal polluted rhizospheres could serve as economical and ecofriendly bioaccumulating agents for removal of Cr(VI).